1998
DOI: 10.1093/ajcn/67.2.240
|View full text |Cite
|
Sign up to set email alerts
|

Citrus fruit supplementation reduces lipoprotein oxidation in young men ingesting a diet high in saturated fat: presumptive evidence for an interaction between vitamins C and E in vivo

Abstract: To determine the effects of vitamin C on cardiovascular risk factors, we studied dietary vitamin C enrichment in 36 healthy male students consuming a diet high in saturated fatty acids. After a 1-mo run-in period during which the subjects consumed approximately 50 mg ascorbic acid/d (low-C diet), half of the subjects were randomly assigned to receive 500 mg ascorbic acid/d for an additional 2 mo (high-C diet). Plasma ascorbic acid increased from 13.5 micromol/L with the low-C diet to 51.7 micromol/L with the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 36 publications
4
51
0
6
Order By: Relevance
“…In our study, the increase in mean plasma ascorbate was similar to the study of Harats et al (1990). The stronger increase in the other studies (Fuller et al, 1996;Harats et al, 1998) may partly be due to a low vitamin C diet and related low plasma ascorbate concentrations. Indeed, the baseline plasma ascorbate concentration in the present study (45720 mmol/l) was higher than that in the above-mentioned studies.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our study, the increase in mean plasma ascorbate was similar to the study of Harats et al (1990). The stronger increase in the other studies (Fuller et al, 1996;Harats et al, 1998) may partly be due to a low vitamin C diet and related low plasma ascorbate concentrations. Indeed, the baseline plasma ascorbate concentration in the present study (45720 mmol/l) was higher than that in the above-mentioned studies.…”
Section: Discussionsupporting
confidence: 88%
“…Further, the bioavailability was found to be incomplete for doses over 200 mg of vitamin C (Levine et al, 1996). The previous studies in healthy smokers on LDL susceptibility for oxidation applied daily doses of 500 mg (Harats et al, 1998), 1000 mg (Harats et al, 1990;Fuller et al, 1996) and 1500 mg (Harats et al, 1990) vitamin C, which resulted in 2.0-2.3-fold (Harats et al, 1990), 3.8-fold (Harats et al, 1998) to 3.9-fold (Fuller et al, 1996) increase in plasma ascorbate levels. In our study, the increase in mean plasma ascorbate was similar to the study of Harats et al (1990).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Diets rich in fruits and vegetables have been shown to increase the resistance of LDL to oxidation (Abbey et al 1995;Harats et al 1998). Recently, we have shown that increased consumption of a carotenoid-rich (i.e.…”
Section: Fruits and Vegetables Ldl Oxidation And Lipoprotein Metabolismmentioning
confidence: 99%